Redesain Kemasan Dalam Meningkatkan Brand Awareness Produk Unggulan Desa Galo-Galo - Hasrul Saleh; Zulfikram Zulfikram; Amrin Sibua; Rinaldin Burahim; E Preti Tikilo; Dayan Jainal (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
Product packaging design is an important factor that can strengthen MSME branding in increasingly competitive business competition. An attractive and quality packaging design differentiates it from competitors. For this reason, community service was carried out to find out the extent to which Galo-Galo Village UKM players understand the importance of product packaging redesign. The aim of this activity is to build brand awareness from the redesign of the product packaging being launched. The method of activity is through socialization and assistance in redesigning product packaging that is more attractive to consumers by choosing one of the superior products. The external target is to create alternative product packaging, one of the superior products, namely Natural Soap, produced by UKM Galo-Galo Village. The results of community service regarding packaging redesign are related to shape, structure, materials, colors, images, typography and design elements with product information so that the product can be marketed. Packaging redesign in the form of redesigning old packaging into new packaging to make it more attractive, so that it has maximum function to wrap, protect, send, issue, store, identify and differentiate a product on the market.